Urban Politics and Sociodemographic Changes in Mexico City’s Urban Center ¿Gentrification or Resettlement? - Díaz Parra, Ibán (Universidad del Rosario, 2016)
In the last decades there have been significant changes in Mexico City’s urban core. The hegemonic thought has often interpreted these changes as a process of building upgrading and resettlement. At the same time, some scholars are denouncing a gentrification process and the substitution of the poorer dwellers for more affluent ones. This paper develops a historical review of the urban center devaluation and revaluation and its relation to more recent sociodemographic changes by exploring the Mexican census. As a result, the research highlights a series of sectors in the urban core where strong public or private investment coincides with the social upgrade of its population.